TELAAH SIMBOL DAN METAFOR: ANTARA TRANSENDENTALISME DAN “SUFISME SEKULER” DALAM KARYA RALPH WALDO EMERSON - Albertine Minderop (Adabiyyāt: Jurnal Bahasa dan Sastra, 2015)
The aim of this study is to show the essence of transcendentalism in the context of the "Divine Light" which is assessed through figurative language style (metaphors and symbols). The scope of research is the study of literature, such as essays, and style; from the point of Transcendentalism philosophy. The theory used is the science of literature -the concepts of figurative language. The point of view is  philosophy of transcendentalism and Sufism. Stages in Sufism are Shari'a, congregations, nature, and ma'rifat. The results showed that Emerson’s essays called transcendentalism contains teachings as "Secular Sufism", focusing on human control efforts. In this case, Emerson Transcendentalism does not require any religious  means, therefore he was called “Secular Sufism”; whereas the teachings of Sufism emphasizes the teachings of religion. Conclusion of the study is the benefit of achieving the "Light Divine," that is, a mental reform that produces "true happiness" and forms a "whole person."